Synthesis of zeolite A by ultrasound irradiation technique - Harun, Mohd Razif (2007)
Synthesization of Zeolite A from colloidal silica by ultrasound irradiation technique was compared with the material obtained by hydrothermal technique. The composition was at molar ratio of 1 Al2O3: 0.85 SiO2: 3.0 Na2O: 200 H2O. X-Ray diffraction (XRD) and Scanning Electron Microscope have been used to characterize the products. Although, XRD pattern of both samples showed typical peaks of zeolite A, intensity of peaks were higher for ultrasound irradiation technique compared to the hydrothermal technique. Moreover, SEM analysis indicated the crystal size of zeolite A synthesized by ultrasound irradiation technique (1.7-5.2Î¼m) was smaller compared to the hydrothermal technique (1.9-5.5 Î¼m). Thus, ultrasound irradiation has a potential to be applied in synthesizing zeolite A.